Determination of tooth size and arch dimension in a pakistani population: a novel approach utilizing digital model - Shahid, Fazal (2015)

(untitled)
The prime aim of this thesis is to develop the norms for tooth size, tooth size ratio (Bolton index), arch dimension, arch length and arch perimeter on subjects of Angle‘s class I (normal) occlusion in Pakistani population. This thesis describes the validity and reliability of digital model measurements, geomorphometrics norms of tooth size and arch dimension analysis by conventional digital caliper and digital stereomicroscope, measurement for Bolton‘ tooth size ratio (intermaxillary tooth size discrepancy) investigation, tooth size and intermaxillary tooth size discrepancy via circumferential tooth size measurements. In order to establish standard norms for the Pakistani population, we investigated the tooth size and arch dimension using conventional digital caliper (DC) and digital stereomicroscope (SM). The sample consisted of 128 subjects ranging in age from 18 to 24 years. Dental models of each subject for maxillary and mandibular arches were scanned via Hirox digital stereomicroscope for the fabrication of the digital models, and the tooth size and arch dimensions were measured via SM scanned digital models. Sex differences were assessed, and interrelationships between different variables were explored within the study group. For the data obtained by SM techniques, the men had statistically significant larger arch dimensions and geomorphometrics norms of tooth size than the women (p<0.05). For the Bolton‘ tooth size ratio (intermaxillary tooth size discrepancy), the sum of anterior tooth size and overall tooth size via SM methods showed statistically significant result in relation sexual disparities (p<0.05). No significant sexual disparities for Bolton‘s anterior ratios (BAR) and Bolton‘s overall ratios (BOR) were observed. This study has established a new reference database of tooth size and arch dimensions via SM for first time on Pakistani population. These norms for tooth size and tooth size ratio will be helpful for clinical treatment planning in dentistry and forensic dentistry.